2017
DOI: 10.1177/2047487317707854
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet and antithrombotic treatment for secondary prevention in ischaemic heart disease

Abstract: Platelets play a key role in the pathogenesis of acute coronary syndromes and this is why antiplatelet drugs are essential, both in the acute phase and in the long-term follow-up in preventing recurrent myocardial infarction, stroke and cardiovascular death. Aspirin is the most used agent and still remains the first choice drug for lifelong administration in secondary prevention after myocardial infarction. Dual antiplatelet therapy, targeting more than one pathway of platelet activation, has significantly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…25 Moreover, as the effect of antiplatelet therapy may depend on the levels of hyperglycaemia, differences in glycaemic control across RCTs may influence the efficacy of the antiplatelet intervention. 26 Low-dose aspirin is recommended together with a P2Y 12 receptor blocker (dual antiplatelet therapy; DAPT) in secondary prevention post-ACS and/or post-percutaneous coronary intervention (PCI) 27 also in DM (Table 1). Aspirin permanently inhibits cyclooxygenase-1 dependent TXA 2 biosynthesis from platelets.…”
Section: Cardiovascular Prevention Post-acute Coronary Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…25 Moreover, as the effect of antiplatelet therapy may depend on the levels of hyperglycaemia, differences in glycaemic control across RCTs may influence the efficacy of the antiplatelet intervention. 26 Low-dose aspirin is recommended together with a P2Y 12 receptor blocker (dual antiplatelet therapy; DAPT) in secondary prevention post-ACS and/or post-percutaneous coronary intervention (PCI) 27 also in DM (Table 1). Aspirin permanently inhibits cyclooxygenase-1 dependent TXA 2 biosynthesis from platelets.…”
Section: Cardiovascular Prevention Post-acute Coronary Syndromementioning
confidence: 99%
“…3,42 Conversely, the stroke rate was generally lower with PCI. 42,44 Repeated MR was consistently lower with CABG, especially at low ( 22) or intermediate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) SYNTAX scores, an indicator of the anatomical complexity of CAD. 42,45 In a metaanalysis including 3052 DM patients, PCI with firstgeneration DES was confirmed to be inferior to CABG on death (14% versus 9.7%; risk ratio (RR) 1.51, 95% CI 1.09-2.10) and MI (10.3% versus 5.9%; RR 1.44, 95% CI 0.79-2.6), and superior on the occurrence of stroke (2.3% versus 3.8%; RR 0.59, 95% CI 0.39-0.90).…”
Section: Revascularisation Strategiesmentioning
confidence: 99%
“…The potency, safety and administration doses for these drugs were all verified through clinical trials. However, the drawback of bleeding is still ineluctable …”
Section: Introductionmentioning
confidence: 99%
“…However, the drawback of bleeding is still ineluctable. [2,9,10] Panax notoginseng (Burk) F.H. Chen is mainly produced from Yunnan province of China, and has been used as a Traditional Chinese Medicine (TCM) for hundreds of years due to its amazing effects on replenishing blood, haemostasis and removing blood stasis.…”
Section: Introductionmentioning
confidence: 99%
“…The ASCEND study (A Study of Cardiovascular Events iN Diabetes) showed that aspirin every day reduces the risk of the first cardiovascular event in high-risk diabetes patients but also that the benefit is counterbalanced by the risk of bleeding. 1 The ARRIVE study, published simultaneously in the Lancet, has not been able to document a benefit of the primary preventive intake of aspirin every day in non-diabetic and lowrisk cardiovascular subjects. 2 The results of the ASCEND study have shown that, when looking at the risk-benefit balance, the absolute benefit of the reduction of serious vascular events, obtained with aspirin, is largely counterbalanced by the increased risk of bleeding.…”
mentioning
confidence: 99%